Incidence of Lymph Node Metastasis in Surgically Staged FIGO IA G1/G2 Endometrial Cancer With a Tumor Size of More Than 2 cm. Issue 3 (March 2017) - Boyraz, Gokhan; Salman, Mehmet Coskun; Gultekin, Murat; Basaran, Derman; Cagan, Murat; Ozgul, Nejat; Yuce, Kunter
Abstract : Objective: The study aims to investigate effect of tumor size on lymphatic spread in patients with low-risk endometrial cancer (EC). Methods: This study included patients with EC who underwent staging surgery with systematic lymphadenectomy between 2002 and 2015 at the Hacettepe University Hospital. Patients with grade 1 or 2 endometrioid type tumor who had 50% or lower myometrial invasion were included. Patients who had no myometrial invasion or had uterine high-risk features (nonendometrioid histology, grade 3, and deep myometrial invasion) were excluded. Results: The study group consisted of 191 patients, and the mean age of the patients was 57.8 years. Of these patients, 124 (64.9%) had tumor size of more than 2 cm and 67 (35.1%) had tumor size of 2 cm or less. Lymph node metastasis was detected in 12 (9.7%) of the 124 patients with tumor size of more than 2 cm. On the other hand, none of the 67 patients (0%) with tumor size of 2 cm or less was found to have lymphatic involvement. Of the factors analyzed for correlation with lymph node metastasis in patients with low-risk EC, the presence of lymphovascular space invasion (LVSI) and primary tumor size were found to be significant predictors of lymphatic spread in univariate analysis ( P < 0.001 and P = 0.009, respectively). In multivariate analysis, tumor size (odds ratio, 6.86; 95% confidence interval, 1.007-infinite; P < 0.05) and LVSI (odds ratio, 14.261; 95% confidence interval, 3.4–59.6; P < 0.001) were 2 independent predictors associated with lymphatic involvement. Conclusions: Our trial supports that tumor size of more than 2 cm and LVSI are 2 independent factors for lymph node metastasis in patients with low-risk EC. Both factors can be used together to select patients with traditional low-risk histologic features who would absolutely benefit from lymph node dissection.